Sourdough : from pastries to gluten-free wholegrain breads - Yoke Mardewi (New Holland Publishers, 2011)
Learn the art of making sourdough bread, pastries, loaves and cakes. Mardewi cover new recipes and techniques with step-by-step guide to making perfect sourdough every time-- even gluten-free!